2016
DOI: 10.1155/2016/3076031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Corneal Temperature and Intraocular Pressure in Healthy Individuals: A Clinical Thermographic Analysis

Abstract: Purpose. To study the geographical distribution of corneal temperature (CT) and its influence on the intraocular pressure (IOP) of healthy human volunteers. Materials and Methods. Fifteen subjects (7 M, 8 F), 33.8 ± 17.4 years old, were enrolled in this pilot, cross-sectional study. Measurements of CT were taken after one hour with closed eyelids (CET) or closed eyelids with a cooling mask (cm-CET) and compared to baseline. Results. If compared to baseline, after CET, average CT significantly increased by 0.56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…By adjusting ambient temperature from 40 to 80°C, the corneal temperature will vary from 37 to 42°C. 16,17 For a given plastic strain of the collagen fibers in the rabbit sclera, the higher the temperature, the greater the strain. 18 The rabbit sclera at 39.5°C permanently strains 1.5% with a stress pressure of only 100 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…By adjusting ambient temperature from 40 to 80°C, the corneal temperature will vary from 37 to 42°C. 16,17 For a given plastic strain of the collagen fibers in the rabbit sclera, the higher the temperature, the greater the strain. 18 The rabbit sclera at 39.5°C permanently strains 1.5% with a stress pressure of only 100 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, biomechanical analyses of the physical properties of the eyes, in particular the cornea, are too complex to obtain a general mechanical model for linking the tissue morphology to their elastic properties and to the flows between the eye and its external environment 11 . The cornea tissue is characterized by the properties of the soft material, in particular 12 13 14 15 16 17 18 19 20 21 22 23 : Heterogeneity in the central-to-peripheral, and anterior-to-posterior dimensions 12 ; Near incompressibility, due to the large amount of water and collagen fibres, with a consequent Poisson’s ratio of the cornea of about 13 0.5; Non-linear constitutive behaviour in relation to the IOP variation 14 ; Viscoelastic and creep behaviour observed in cyclic tests 15 ; Structural anisotropy generated by the oriented collagen fibrils 16 . …”
mentioning
confidence: 99%
“…Corneal temperature values of 34 C and above were reported multiple times in literature, in particular as a target threshold for diagnostic purposes. 1,4,17,27,34 Other studies 1,6,49 reported that temperatures in the range 32.0-33.5 C were found across the corneal area. The hysteresis of the sensor was evaluated by temperature swing in the range 33.0 C to 38.0 C, and from 32.0 C to 33.0 C, with a stabilization time of 10 minutes at each 1.0 C step, showing average variations of z8 nm between advancing and receding measurements.…”
Section: Discussionmentioning
confidence: 93%
“…Liquid crystals embedded in contact lenses were optically characterized, showing a consistent behavior. The readout principle was shown on an ex vivo porcine eye, where readouts were compared with infrared thermal measurements, resulting in an average difference of 0.3 C. Contact lens temperature sensors may be used to monitor dry eye disease (0.5 C decrease), 26 post-corneal transplant infections (1 C increase), 34 IOP modications (0.5 C variations), 17 as well as to monitor ocular temperature variations in individuals for research purposes, to contribute to trace the connes of healthy/unhealthy ocular temperature values, and external factors inuencing the same. Scleral lenses are an attractive device for point-of-care medicine applications, being them used daily by patients suffering from a variety of diseases where corneal temperature monitoring may be desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation